GROUND SUBSIDENCE CAUSED BY EARTHQUAKE TYPE EXCITATION - H. B. Poorooshasb; A. Noorzad (Lowland Technology International, 1999)
The extended CANAsand constitutive model, which incorporates the newly proposed concept of the "Compact State", is used in conjunction with the ID technique to evaluate the total subsidence of a sandy deposit. The ID technique is a simple numerical procedure developed recently. The results of the analysis clearly demonstrate the importance of the initial void ratio of the deposit, its permeability and the depth of the overburden on the magnitude of the subsidence of the layer.